Study of some immunological effects of methotrexate in people with rheumatoid arthritis - kareem, Faten; Thamer, Wijdan (Al-Qadisiyah Journal of Pure Science, 2019)
The aim of this study was to determine the effect of rheumatoid arthritis on some immunological criteria in women with rheumatoid arthritis at M arjan Specialist Hospital in Babil governate for the period from 20/10/2018 until 20/4/2019, when 90 samples of women aged between 25 to 55 years old into three groups: the first (30) women with rheumatoid arthritis Calming treatments. And the second (30) of women with rheumatoid arthritis who received methotrexate treatment. The third sample (30) included a sample of nonRA patients representing control. 5 mL of venous blood was withdrawn and placed in a test tube and then placed in a centrifuge to separate the serum and perform immunological tests (Inter Lockin 4, Inter Lockin 6) Results showed a significant increase of P <0.0.5 in the level of interleukin (4.6) in infected women compared to the control group. We conclude from the study that the incidence of rheumatoid arthritis had a significant effect on the level of interleukins (6.4) in women, and was the highest difference in the group of women who use analgesics as a treatment. The study showed that MTX had a significant effect in reducing measured parameter levels compared to control group